Pictogramas como recurso para el desarrollo del lenguaje verbal - Casa Iza, Jessica Pamela (2016)
The following work is made in order to achieve good development in verbal language, for each child initial -level of parallel "B" of the educational unit "San José de Guaytacama" in which it aims through various activities to be undertaken using pictographs as a resource. To achieve that in this way the boy and girl have a better development in reading and at the same time in your communication. The family and institutions are most important since they directly influence the development of each of the children in their process of learning even more at the initial level so that the activities to done in this institution is necessary as an educational tool for teacher education since this will help for the teacher to appreciate and value the importance that provide the pictograms and can use them for the development of learning, helping toddler to improve your attention, because the senses are the channel of communication with the outside and above all through the sense of sight is where the child captures more information, learn faster in the same way parents are partakers because they benefit in carrying out these activities for the development of their children that is where born the realization of this project pictograms as a resource for the development of verbal language.